Outcome of Wingspan Stent Using Aggressive Post-stent Balloon Dilation for Intracranial Atherosclerosis Stenosis - Perng, Pang-Shuo; Sun, Yuan-Ting; Wang, Hao-Kuang; Shih, Yu-Hsiang; Lee, Jung-Shun; Wang, Liang-Chao; Huang, Chih-Yuan (Frontiers in Neurology, 2021)
Background Wingspan stent has gained interest for better long-term outcomes for intracranial atherosclerosis disease (ICAD). However, in-stent restenosis still presents as a problem and may cause postoperative neurological events. We aimed to find a way to prevent in-stent restenosis. Method Patients with stenosis >70% ICAD were treated with wingspan stent and were retrospectively reviewed. The patients were separated into two groups: one with post-dilation angioplasty and the other without post-dilation angioplasty. The outcomes of wingspan stenting were compared immediately after the surgery and at a 1-year follow-up. Results Overall, 28 patients were included for analysis, with 15 patients undergoing post-dilation angioplasty and 13 patients not undergoing the procedure. The extent of stenosis was significantly lower in the post-dilation group than in the no post-dilation group, both immediately after the surgery (14.8 ± 10.2% vs. 28.5 ± 14.5%, p < 0.01) and at 1-year follow-up (25.8 ± 18.0 % vs. 50.1 ± 23.2%, p < 0.01). The post-dilation method immediately expanded the stent diameter (2.89 ± 0.48 vs. 3.05 ± 0.44 mm, p < 0.001), and the diameter still increased at 1-year follow-up (3.05 ± 0.44 vs. 3.12 ± 0.43 mm, p < 0.01) due to self-expandable property of the wingspan. Similarly, in no post-dilation group, the stent size was also increased (2.70 ± 0.67 vs. 2.80 ± 0.64, p < 0.01). However, at one year follow up, the luminal diameter was stationary in post-dilation group (2.36 ± 0.73 vs. 2.46 ± 0.82 mm, p = 0.88) and decreased in no post-dilation group (2.24 ± 0.56 mm vs. 1.60 ± 0.79 mm, p < 0.01). The periprocedural complication rate was similar between the groups. Conclusion The post-dilation method can be feasibly performed and can offer better stent expansion and apposition in the wingspan system. By applying this technique, we might prevent in-stent restenosis and improve neurological outcomes.